Successful mechanical thrombectomy of an intermediate-high risk acute pulmonary embolism using the Alpha Vac aspiration catheter - Bright Benfor, MD; Jacob B. Watson, MD; Tarundeep Singh, MD; Eric K. Peden, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
Large-bore aspiration thrombectomy is emerging as a promising alternative for thrombus removal in acute pulmonary embolism (PE). In this article, we report a successful case with the newly approved AlphaVac F1885 device in a 76-year-old patient presenting with an intermediate- to high-risk acute PE. Preoperative imaging demonstrated bilateral PE with a modified miller index of 30 and an right ventricle-to-left ventricle ratio of 2.1. Mechanical thrombectomy was performed under local anesthesia with mild sedation. The pulmonary artery pressures decreased from 85/27 to 46/13 immediately after thrombectomy. The postoperative course was notable for marked symptom improvement and repeat imaging showed a 63% decrease in clot burden with a decrease in right ventricle-to-left ventricle ratio to 1.3.